2013
DOI: 10.1002/rrq.57
|View full text |Cite
|
Sign up to set email alerts
|

Defining Success in Adult Basic Education Settings: Multiple Stakeholders, Multiple Perspectives

Abstract: This study employed quantitative and qualitative research approaches to investigate what constitutes “success” in Adult Basic Education (ABE) programs from the perspectives of multiple educational stakeholders: the state funding agency, the teachers, and the students. Success was defined in multiple ways. In the quantitative section of the study, we computed classroom value-added scores (used as a metric of the state’s definition of success) to identify more and less effective ABE classrooms in two Florida cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…Adult basic education programs are designed to provide instruction to adults (ages 16 and older and not concurrently enrolled in K-12 education) in order to complete a General Educational Development certificate (GED; or high school equivalency degree). These programs cater to a heterogeneous group of learners in terms of age, race/ethnicity, learning disability status, English language learner status, educational background, and motivations for pursuing a GED certificate ( Lesgold and Welch-Ross, 2012 ; Tighe et al, 2013 ). Many of these programs suffer from under-funding, over-crowding, high teacher turnover rates, high student attrition rates, and a lack of empirically based, standardized curricular materials and instructional practices ( Lesgold and Welch-Ross, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Adult basic education programs are designed to provide instruction to adults (ages 16 and older and not concurrently enrolled in K-12 education) in order to complete a General Educational Development certificate (GED; or high school equivalency degree). These programs cater to a heterogeneous group of learners in terms of age, race/ethnicity, learning disability status, English language learner status, educational background, and motivations for pursuing a GED certificate ( Lesgold and Welch-Ross, 2012 ; Tighe et al, 2013 ). Many of these programs suffer from under-funding, over-crowding, high teacher turnover rates, high student attrition rates, and a lack of empirically based, standardized curricular materials and instructional practices ( Lesgold and Welch-Ross, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly important in the context of adult basic education where learners' goals, perspectives and definitions of success may not be related to the accountability goals of other stakeholders. 29 One limitation of this study is that we only interviewed participants from health literacy classes and do not know how much of the observed advantage was a result of the health literacy intervention. We also did not interview participants who dropped out of the program, and our sample differed from the larger randomised controlled trial sample on self-reported employment status and reasons for taking the course.…”
Section: Strengths and Weaknesses Of The Studymentioning
confidence: 99%
“…Adults with low literacy skills tend to vary not only in demographic variables (age, gender, and race/ ethnicity), but also in terms of educational backgrounds, learning disabilities, and primary languages (English or other) as well as their motivation for taking part in adult literacy courses (National Research Council 2011). For instance, adults with low literacy may want to improve their reading skills out of a wish to become proficient in English, as a pre-requisite for pursuing a college degree, to get promoted in career or job training, because of encouragement from family, or a desire to improve their quality of life (Malicky and Norman 1994;Tighe et al 2013). Due to the heterogeneity of the population, more research is necessary to better understand how to tailor instruction and materials to meet the various needs of the individuals in this group.…”
Section: Characteristics Of Adult Learnersmentioning
confidence: 99%